1999
DOI: 10.1056/nejm199907293410504
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Urinary Lactate:Creatinine Ratio for the Early Identification of Newborn Infants at Risk for Hypoxic–Ischemic Encephalopathy

Abstract: Measurement of the urinary lactate: creatinine ratio soon after birth may help identify infants at high risk for hypoxic-ischemic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
1
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 30 publications
1
66
1
3
Order By: Relevance
“…S100β protein concentrations in moderately/severely asphyxiated neonates were significantly higher than in controls and mildly asphyxiated infants. Huang et al [13] reported that the urinary lactate:creatine ratio predicts HIE within 6 h with 1 H nuclear magnetic resonance spectroscopy, but magnetic resonance spectroscopy is not practical in most clinical situations; a useful indicator for HIE should be specific even earlier, and requires a rapid and readily available laboratory technique. Besides this, infants with asphyxia often have oliguria, and urine sampling may not be possible [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S100β protein concentrations in moderately/severely asphyxiated neonates were significantly higher than in controls and mildly asphyxiated infants. Huang et al [13] reported that the urinary lactate:creatine ratio predicts HIE within 6 h with 1 H nuclear magnetic resonance spectroscopy, but magnetic resonance spectroscopy is not practical in most clinical situations; a useful indicator for HIE should be specific even earlier, and requires a rapid and readily available laboratory technique. Besides this, infants with asphyxia often have oliguria, and urine sampling may not be possible [19].…”
Section: Discussionmentioning
confidence: 99%
“…The asphyxia group consisted of 40 subsequently full-term newborn infants (gestational age, 37-42 weeks) who fulfilled at least three of the following conditions: fetal bradycardia with a heart rate of less than 100 beats per minute, late decelerations, or an absence of heart-rate variability; thick, meconium-stained amniotic fluid; an Apgar score of 6 or less at 5 min; a need for resuscitation for more than 1 min with positive-pressure ventilation and oxygen immediately after birth [13]. The exclusion criteria were maternal drug addiction, congenital infections, or perinatal infection, including chorioamnionitis.…”
Section: Asphyxia Groupmentioning
confidence: 99%
“…The following study groups were enrolled: (1) neonatal controls: serum samples from term healthy control infants following normal delivery with normal Apgar scores, neurological examination and postnatal course, and (2) infants exposed to perinatal asphyxia (PA): infants with at least 2 of the following criteria were eligible for inclusion according to the criteria of Huang et al [5]: (i) evidence or suspicion of hypoxic-ischaemic injury based on a history of foetal distress, i.e. type II dips, loss of beat-to-beat variability on the cardiotocograph and/or abnormal scalp pH; (ii) need for resuscitation after birth, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al [56] measured urinary lactate/creatinine ratios in asphyxiated infants soon after birth, using proton nuclear magnetic resonance. 1H nuclear magnetic resonance (NMR) spectroscopy indicated an elevated ratio within 6 hours after birth, with a sensitivity of 94% and a specificity of 100% in predicting HIE.…”
Section: Other Biochemical Markers Of Perinatal Asphyxiamentioning
confidence: 99%